Lubuk Larangan sebagai Manifestasi Paradigma Ekologi Baru: Analisis Sosiologi Ekologi - Rahma Hayati Harahap; Siregar Riskyah Maulida; Zeni Eka Putri (Talenta Publisher, 2026)
Lubuk Larangan, a local wisdom practice in Sumatra, Indonesia, is a traditional fisheries management system that prohibits fishing in certain river zones to preserve natural resources. This article analyzes this practice through the lens of ecological sociology, using the perspectives of William R. Catton Jr. and Riley E. Dunlap, comparing the Human Exemptionalism Paradigm (HEP) with the New Ecological Paradigm (NEP). This qualitative research combines a literature review of NEP and HEP theories with fieldwork in Jambi, Riau, Mandailing Natal, and Solok Selatan (2022–2024), using secondary data from observations, interviews, and research reports. The findings indicate that Lubuk Larangan reflects the NEP by integrating ecological variables into the social structure, increasing fish biodiversity by up to 50% in the prohibited zone, and strengthening social capital through communal rituals. However, challenges of modernization such as urbanization and oil palm plantations threaten the sustainability of this practice. The article concludes that Lubuk Larangan offers a globally relevant model for sustainability, with recommendations for the integration of national policies and digital research.